UPAYA PENCEGAHAN KEKERASAN DI LEMBAGA PESANTREN MELALUI GRAND STRATEGY NASIONAL - Novita Febrianti; Anisa Hidayatul Musyarofah; Irma Lupita Sari (Program Studi Manajemen Pendidikan Islam, 2025)
Pesantren, as traditional Islamic educational institutions in Indonesia, play a strategic role in shaping the religious, social, and cultural character of society. Over time, pesantren have not only functioned as centers for teaching classical Islamic texts (kitab kuning) and preserving religious traditions, but have also become agents of social transformation integrated with national education policies. The 2025 Nahdlatul Ulama (NU) Grand Conference (Konbes) recommended the formulation of a Grand Strategy to address violence in educational institutions, including pesantren, in response to the increasing cases of violence that affect the quality of education. This Grand Strategy emphasizes the importance of collaborative, systematic, and Islamic value-based approaches to create a safe, inclusive, and moderate educational ecosystem. The implementation of this strategy is reflected in various NU programs, such as the Halaqah Fiqh al-Hadlarah (Fiqh of Civilization Forum), which aims to strengthen the intellectual capacity and ethical integrity of religious scholars, while simultaneously preventing violence rooted in power relations within pesantren. This study highlights that NU’s National Grand Strategy serves both preventive and transformational functions, enabling pesantren to maintain their traditional identity while adapting to social, technological, and policy dynamics.